2001
DOI: 10.1248/bpb.24.491
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic Receptor Binding Characteristics in Rat Tissues after Oral Administration of Oxybutynin and Propiverine.

Abstract: In conclusion, the present study has shown that oxybutynin and propiverine, after oral administration, bind significantly to muscarinic receptors in tissues such as the bladder, which is the target organ for the treatment of urinary incontinence, and that oxybutynin appears to exhibit long-term binding to muscarinic receptors in the salivary gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Thus, the selectivity for the urinary bladder over the brain was relatively low for oxybutynin, suggesting a high feasibility of CNS side effects at pharmacological doses to treat OAB. This finding seems to be in a reasonable agreement with previous observations of oxybutynin shown by pharmacological (Sugiyama et al, 1999) and ex vivo receptor binding (Oki et al, 2001) studies in rats and also by clinical studies (Pietzko et al, 1994;Katz et al, 1998;Todorova et al, 2001;Ancelin et al, 2006). In fact, CNS side effect by oxybutynin occurred in patients with OAB and in older subjects receiving this drug (Scheife and Takeda, 2005;Kay et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the selectivity for the urinary bladder over the brain was relatively low for oxybutynin, suggesting a high feasibility of CNS side effects at pharmacological doses to treat OAB. This finding seems to be in a reasonable agreement with previous observations of oxybutynin shown by pharmacological (Sugiyama et al, 1999) and ex vivo receptor binding (Oki et al, 2001) studies in rats and also by clinical studies (Pietzko et al, 1994;Katz et al, 1998;Todorova et al, 2001;Ancelin et al, 2006). In fact, CNS side effect by oxybutynin occurred in patients with OAB and in older subjects receiving this drug (Scheife and Takeda, 2005;Kay et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…It was shown that only the higher dose (24.8 mol/kg i.v.) of propiverine induced CNS effects in rats and bound to muscarinic receptors in rat brain (Oki et al, 2001). Thus, propiverine may exhibit lower incidence of CNS effects than that of oxybutynin in patients with OAB.…”
Section: Discussionmentioning
confidence: 99%
“…Similar data on these agents were reported in human muscarinic receptor subtypes expressed in Chinese hamster ovary cells (Wuest et al, 2006). Furthermore, oral administration of propiverine at pharmacologically relevant doses (24.8 -248 mol/kg) (Nomura et al, 1989;Oki et al, 2001) produced a significant increase in K d values for [ 3 H]NMS binding in the bladder. The significant increase in K d values was seen 3 h after the oral administration of this drug at the low dose (24.8 mol/kg) and 1 to 12 h at higher doses (74.3, 248 mol/kg).…”
Section: Discussionsupporting
confidence: 73%
“…Previous studies using radioreceptor assay demonstrated that imidafenacin exerts more selective and longer-lasting distribution in the bladder than in salivary gland and colon in rats (Yamada et al 2011), whereas propiverine and solifenacin distribute in the salivary gland or in other antimuscarinic side effect-related tissue as well as in the bladder (Oki et al 2001(Oki et al , 2005. Yamada et al (2011) reported that imidafenacin excreted in urine may contribute to its selective and long-lasting distribution in the bladder because imidafenacin showed a significant binding to bladder muscarinic receptors in rats following its intravesical instillation at a concentration which corresponds to its urine concentration after oral administration in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%